WTO and policy space for agriculture and food security: issues for China and India - Sachin Kumar Sharma (Agricultural Economics Research Review, 2023)
The US has challenged the product-specific support to foodgrains by China in the WTO claiming that China has breached its commitments under WTO by providing more than US$100 billion as productspecific support to wheat, rice and corn in 2015. The main issue is the price support backed procurement of foodgrains for food security purposes. India too implements this type of policy, this case also has implications for India as well. China implements the Minimum Procurement Price policy for price stabilization, protecting farmers from price volatility and manage food supplies. India too procures foodgrains mainly rice and wheat at Minimum Support Price (MSP) for distribution to the poor at subsidised prices through the public distribution system (PDS). In fact, with 320 million people in India and China being undernourished, ensuring food security remains a major concern in both the countries. To verify US claim about the extent of domestic support in China, in this paper we examine the policy space available for product-specific support in China and India. Our findings show that as against the claim of product-specific support of more than US$100 billion it is just US$17 billion. We also highlight different aspects of food security, domestic support in US and the need for a level-playing field in international trade.